O-77 Effects of advance care planning in patients with cancer. results from a systematic review. (1st September 2015) - Schildmann, Jan; Bausewein, C; Krones, Tanja; Simon, A; Simon, ST; Voltz, R; Weber, M; Weis, J; Schmitten, Jürgen in der
Abstract : Background: Advance Care Planning (ACP) is a systematic and interprofessional approach of communicating and implementing advance health care planning between patients, relatives and persons involved in the healthcare of a particular patient. Aim: The aim of this contribution is to assess the effectiveness of ACP in patients with cancer. Methods: Search in MEDLINE, EMBASE, PsycINFO and Cochrane Library. Criteria for inclusion were patients with cancer, ACP defined as communication about advance healthcare planning facilitated by healthcare professionals, a control group without ACP and measurement of patient oriented outcomes. All abstracts and selected publications were evaluated by two researchers independently. Results: Out of 572 hits we included 11 relevant studies with a total of 4060 patients. ACP often was part of a complex intervention and was not specified in more detail. The results of the studies included in this review indicate that ACP in patients with cancer is associated with improved psychological wellbeing, improved quality of life, less informational needs, a higher chance of preference sensitive care, less intensive care measures in the last phase of life and better knowledge regarding the rates for success of resuscitation. Discussion: The findings of this systematic review suggest that ACP in patients with cancer has positive patient oriented outcomes. However given the heterogeneous and often vague definitions of ACP the findings of the different studies are difficult to compare. Conclusion: High quality randomised trials are needed to corroborate current evidence regarding the effectiveness of ACP in oncology.